Stee Enterprise / Akbar Ali Rudin ... [et al.] - Rudin, Akbar Ali; Mahmud, Elna Marlina; Awg Jaafar, Fareezal; Jahin, Fazwani; Madan Yukri, Suhamdan (2011)
At the present time, sugar is the highest demand from people that always being preferred by all kinds of customers and different standard of living. Unfortunately there is a limit choice for customers out there and in order to liberate from this condition we decided to set our foot in Stevia agriculture as a substitute for sugar and more healthy.